2010
DOI: 10.2174/156652410790963295
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Nucleic Acids as a Potential Source for Cancer Biomarkers

Abstract: Since the association of circulating DNA level changes with tumor growth was discovered many attempts have been made to develop the sensitive and robust blood-based tests for early tumor diagnostics. Both genomic as well as mitochondrial DNA quantification in the circulation have been extensively evaluated as a diagnostic and prognostic tool to monitor cancer therapy. Cell-free DNA bearing the same genetic and epigenetic changes as the tumor tissues were shown to be detectable in plasma / serum of cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 170 publications
1
44
0
3
Order By: Relevance
“…Recent studies have shown that aberrant DNA methylation, which typically occurs before patients develop clinical manifestations and radiographic evidence, can be detected in cellfree serum (Vlassov et al, 2010;Liggett et al, 2011;Zhang et al, 2013). The amount of available cell-free serum DNA is often very low.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that aberrant DNA methylation, which typically occurs before patients develop clinical manifestations and radiographic evidence, can be detected in cellfree serum (Vlassov et al, 2010;Liggett et al, 2011;Zhang et al, 2013). The amount of available cell-free serum DNA is often very low.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is being tested as potential diagnostic marker for a variety of cancers such as prostate, colorectal, cervical, lung, bladder cancer and leukemias. [39][40][41][42][43] Whereas hypermethylation of tumor suppressor genes is a widely accepted mechanism for tumor progression, DNA hypermethylation in response to UTI infection is currently an understudied field and no DNA methylation based biomarker for future UTI infection susceptibility exists. Our goal is to identify candidate regions as potential biomarkers for UTI proclivity, as well as reveal new candidate mechanisms associated with UTI pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…RF, reference; ARMS, amplification refractory mutation system; qPCR, quantitative polymerase chain reaction. general rule, the mismatched bases are often designed in the last 3 bp of the ARMS primer to discriminate between the wild-type and the mutant alleles (26)(27)(28). Notably, in the present study, the rs1050171 was observed to be located in the eighth base from the 3' end of the ARMS primer, and the results revealed that it really affected the sensitivity of T790M mutation detection, particularly in samples with low mutation rates.…”
Section: Discussionmentioning
confidence: 57%